A Dual-Motor Actuator for Ceiling Lift with High-Force and High-Speed Capabilities - Ian Lalonde; Jeff Denis; Mathieu Lamy; Alexandre Girard (Actuators)
Patient transfer devices allow for passive movement of patients in hospitals and care centers. Instead of hoisting the patient, it would be beneficial in some cases to assist their movement, enabling them to move by themselves and reducing hospitalization time. However, patient assistance requires devices capable of precisely controlling output forces at significantly higher speeds than those used for patient transfers alone, and a single-motor solution would be over-sized and would show poor efficiency for accomplishing both functions. This paper presents a ceiling robot, using a dual-motor actuator and adapted control schemes, that can be used to transfer patients, assist patients in their movement, and help prevent falls. The prototype is shown to be able to lift patients weighing up to 318 kg and to assist a patient with a desired force of up to 100 kg with a precision of 7.8%. Also, a smart control scheme to manage falls is shown to be able to stop a patient who is falling by applying a desired deceleration.